Enhancing educational administration based on Taoist thought of higher vocational colleges in Hebei Province - Zhang, Yuyu; Siththada, Thada; Wang, Xiaoting (วารสารการวิจัยการบริหารการพัฒนา, 2025)
This paper aims to: 1) explore the impact mechanism of Taoist thought on the educational management practice of higher vocational colleges in Hebei Province; 2) identify the key factors affecting the management effectiveness of higher vocational education through empirical analysis; 3) construct an optimization model for higher vocational education management based on Taoist philosophy. This study adopts a mixed research method design, integrating quantitative questionnaire surveys and qualitative in-depth interviews. The theoretical framework is based on the core management ideas of Taoism (including "rule by inaction", "Tao follows nature", "yin and yang balance", etc.), focusing on the field of higher vocational education management. The research subjects adopt a stratified random sampling method, and 501 educational managers and full-time teachers from 56 higher vocational colleges in Hebei Province are selected as the research sample. The research tools include: 1) a Likert five-level scale questionnaire containing 105 items; 2) a semi-structured interview outline; 3) a literature analysis tool. The data analysis methods include: descriptive statistics, exploratory factor analysis (EFA) and principal component analysis (PCA) are used for quantitative data using SPSS software; qualitative data are coded and themes are extracted using content analysis. The study found that: 1) The Taoist concept of "ruling by doing nothing" can significantly improve management flexibility (factor loading 0.73-0.85), but a corresponding responsibility constraint mechanism needs to be established; 2) The cumulative variance explanation rate of the 7 common factors extracted by exploratory factor analysis reached 85.78%, proving that Taoist management thought has multidimensional construct validity. The theoretical contribution of this study lies in expanding the application paradigm of traditional Chinese philosophy in modern education management. The practical significance is reflected in providing higher vocational colleges with an innovative solution that integrates traditional wisdom with modern management needs, which has important reference value for improving the effectiveness of education governance.